Interactive Effects of Apolipoprotein E ε4 and Triiodothyronine on Memory Performance in Patients With Subjective Cognitive Decline - Lee, Jin San; Soh, Yunsoo; Kim, Hyug-Gi; Lee, Kyung Mi; Kwon, Young Nam; Yoon, Sung Sang; Park, Key-Chung; Rhee, Hak Young (Frontiers in Medicine, 2020)
Background: The aim of the present study was to investigate the associations between thyroid hormones, cognitive performance, and apolipoprotein E (APOE) genotype in euthyroid patients with subjective cognitive decline (SCD). Methods: We recruited 197 euthyroid patients that fulfilled the criteria for SCD. All participants were classified into APOE ε4 carriers and non-carriers based on the presence of the APOE ε4 allele. Patients with SCD who had the APOE ε2/ε4 genotype were excluded from the study. We then performed correlation and regression analyses to evaluate the associations between cognitive performance and thyroid hormones in APOE ε4 carriers and non-carriers. Results: We found no significant differences in cognitive function between APOE ε4 carriers and non-carriers. However, higher levels of triiodothyronine (T3) were associated with better verbal memory performance (immediate and delayed recall tasks) in APOE ε4 carriers, whereas a negative association was found in APOE ε4 non-carriers. Furthermore, there was a significant interactive effect of APOE ε4 status and T3 levels on verbal memory performance (immediate and delayed recall tasks). Conclusions: These findings suggest that in patients with SCD, T3 might have a protective effect on memory in those who are APOE ε4 carriers. The differential susceptibility hypothesis would thus support a gene-by-hormone crossover interaction between APOE ε4 allele and T3 in this study. Early identification and intervention of high-risk individuals for cognitive decline is important to establish new strategies for preventing dementia.